Incidence and Molecular Identification of Apple Necrotic Mosaic Virus (ApNMV) in Southwest China - Wensen Shi; Rundong Yao; Runze Sunwu; Kui Huang; Zhibin Liu; Xufeng Li; Yi Yang; Jianmei Wang (Plants, 2020)
Apple mosaic disease has a great influence on apple production. In this study, an investigation into the incidence of apple mosaic disease in southwest China was performed, and the pathogen associated with the disease was detected. The results show that 2869 apple trees with mosaic disease were found in the Sichuan, Yunnan, and Guizhou Provinces, with an average incidence of 9.6%. Although apple mosaic virus (ApMV) is widespread in apples worldwide, the diseased samples were negative when tested for ApMV. However, a novel ilarvirus (apple necrotic mosaic virus, ApNMV) was identified in mosaic apple leaves which tested negative for ApMV. RT-PCR analysis indicated that ApNMV was detected in 322 out of 357 samples with mosaic symptoms. Phylogenetic analysis of coat protein (CP) sequences of ApNMV isolates suggested that, compared with ApMV, ApNMV was closer to prunus necrotic ringspot virus (PNRSV). The CP sequences of the isolates showed the diversity of ApNMV, which may enable the virus to adapt to the changeable environments. In addition, the pathology of mosaic disease was observed by microscope, and the result showed that the arrangement of the tissue and the shape of the cell, including the organelle, were seriously destroyed or drastically changed.